Understanding the Literature on Advertising Ethics Using Morphological Analysis - Franklin, Jyothis Maria; Ramanathan, Jayasankar (Indian Journal of Marketing, 2025)
Purpose : This study reviewed the literature on advertising ethics and identified research gaps to provide scope for future work. Design/Methodology/Approach : The relevant literature was identified through a search of Scopus and Web of Science. The final sample of 174 articles was carefully read to determine dimensions and variants, which were used in morphological analysis to construct a cross-consistency matrix and obtain a comprehensive understanding of the domain of advertising ethics. The cross-consistency matrix was used to identify explored and unexplored areas of study. Findings : A comprehensive morphological analysis framework, encompassing six dimensions and 27 variants of advertising ethics research was constructed, leading to the identification of 87 research gaps. Practical Implications : Managers can use the MA framework as a guide for understanding advertising ethics and acting accordingly. Researchers can utilize the framework and the identified research gaps to extend the literature. Originality/Value : This study is the first in the advertising ethics literature to construct a morphological analysis framework. A comprehensive literature search was undertaken by searching both Scopus and Web of Science databases.